Exploring How Parental Encouragement Affects Self-Esteem Through Self-Advocacy in Adolescents with Disabilities - Yildiz, Emre; Hoffmann, Clara; Antoniou, Nikos (KMAN Counseling & Psychology Nexus, 2025)
This study aimed to investigate the relationship between parental encouragement and self-esteem in adolescents with disabilities, with a particular focus on the mediating role of self-advocacy. The study employed a descriptive correlational design involving 421 adolescents with disabilities in Germany, selected based on the Morgan and Krejcie sample size table. Standardized instruments were used to assess the key variables: the Perceptions of Parents Scale (POPS) for parental encouragement, the Self-Advocacy Scale for Youth with Disabilities (SAS-YD), and the Rosenberg Self-Esteem Scale (RSES). Data were analyzed using SPSS-27 for descriptive statistics and Pearson correlation, and AMOS-21 was utilized for Structural Equation Modeling (SEM) to test the mediation model. Assumptions of normality, linearity, and multicollinearity were confirmed prior to analysis. Descriptive statistics indicated relatively high levels of perceived parental encouragement (M = 5.74, SD = 0.63), moderate self-advocacy (M = 4.31, SD = 0.71), and high self-esteem (M = 3.28, SD = 0.62). Pearson correlation analysis revealed significant positive relationships between parental encouragement and self-advocacy (r = .46, p < .001), parental encouragement and self-esteem (r = .39, p < .001), and self-advocacy and self-esteem (r = .52, p < .001). The structural model showed good fit indices (χ² = 94.78, df = 48, CFI = 0.97, RMSEA = 0.047), and self-advocacy was found to partially mediate the relationship between parental encouragement and self-esteem. The total effect of parental encouragement on self-esteem was β = 0.50 (p < .001), with a direct effect of β = 0.28 and an indirect effect of β = 0.22 through self-advocacy. The findings highlight the crucial role of parental encouragement in fostering self-esteem among adolescents with disabilities, both directly and through the development of self-advocacy skills, suggesting the need for family-centered interventions to enhance youth empowerment.